PATHOGENETIC MECHANISMS OF THROMBOEMBOLIC COMPLICATIONS OF THE METABOLIC SYNDROME IN PREGNANCY - A. V. Khromylev; A. D. Makatsariya (Акушерство, гинекология и репродукция)
Prevalence of the metabolic syndrome (MS) is growing all over the world, including women of reproductive age. There is evidence that the presence of MS is associated with hypercoagulation, deficiency in the system of fibrinolysis, increase in platelets activity and, as a consequence, an increased risk of thrombosis. Nowadays genetic and metabolic disorders that underlie the relationship between MS and thromboembolic complications are under active study.